1996
DOI: 10.1071/ea9960529
|View full text |Cite
|
Sign up to set email alerts
|

Estimations of pasture and grain intake of prepartum single- and twin-bearing ewes

Abstract: One hundred and thirty-one pregnant, parous Border Leicester x Merino ewes at pasture were supplemented with a mixture of lupin and oat grain for a minimum of 3 weeks prepartum, and an average of 1 week post-partum in a lamb production experiment. Supplement was group-fed daily at a rate of 400 g/ewe. Pasture and grain intake were determined on 1 day, at an average 7 days prepartum. On an individual ewe basis, there was considerable variation in supplement intake with 11% of ewes consuming <200 g/day and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…This demonstrates the difficulty in achieving adequate nutrition in extensive commercial conditions during late pregnancy and lactation for twin-bearing ewes. Others have suggested that it is not necessary to feed twin-bearing ewes separately from single-bearing ewes due to their ability to take advantage of supplements by eating more supplement and eating less pasture (Holst et al 1996). Our results contradicted this conclusion as it was not possible to maintain twin-bearing ewe condition perinatally even with separate feeding.…”
Section: Ewe Productioncontrasting
confidence: 57%
“…This demonstrates the difficulty in achieving adequate nutrition in extensive commercial conditions during late pregnancy and lactation for twin-bearing ewes. Others have suggested that it is not necessary to feed twin-bearing ewes separately from single-bearing ewes due to their ability to take advantage of supplements by eating more supplement and eating less pasture (Holst et al 1996). Our results contradicted this conclusion as it was not possible to maintain twin-bearing ewe condition perinatally even with separate feeding.…”
Section: Ewe Productioncontrasting
confidence: 57%
“…Although lithium salts have pharmacological and toxic effects and can cause feed aversion (Du Toit et al 1991;Suharyono 1992), the amounts necessary to cause these effects in ruminants are much greater than the amounts generally required as a marker. Lithium salts have been used as a marker of supplement intake for grazing sheep (Suharyono 1992;Kahn 1994;Holst et al 1996) and cattle (Dixon and Petherick 1996;McLennan 1999).…”
Section: Introductionmentioning
confidence: 99%